Biological indicators and commercial exploitation of main fish and river crayfish species of the Zaporizhzhia (Dnipro) reservoir - Marenkov, Oleh; Nesterenko, Oleh; Borovyk, Ivan; Gamolin, Andrey; Shmagailo, Mykola; Kapshuk, Natalia (ScienceRise: Biological Science, 2024)
Aim: To analyze and summarize the biological indicators of the main industrial fish and river crayfish species in the Zaporizhzhia (Dnipro) reservoir under conditions of fishery exploitation. Methods: Biological analysis of fish was conducted according to classical methods in ichthyology, using the following parameters: standard and absolute body length, individual mass, gender, feeding coefficient. Crayfish, caught in fishing gear, underwent morphometric measurements to determine individual mass and gender. Biological sampling was carried out during the vegetation period of 2023 during both control and commercial fishing in the Zaporizhzhia (Dnipro) reservoir at three sites differing in hydrology and degree of anthropogenic impact. Research results: According to the data from the Department of the State Agency of Reclamation and Fisheries Management in Dnipropetrovsk Oblast, during 2023, 140,504 tons of fish were caught in the Zaporizhzhia (Dnipro) reservoir, nearly 8 times less than in 2021. In 2021, 1078.25 tons of aquatic resources were caught, which is 8 % less than in 2020. Silver carp was the dominant fish species in 2022, accounting for 80.5 % of the total catch in the reservoir. Herbivorous fish species accounted for 5.4 % of the catch, roach - 3.3 %, bream - 2.3 %, perch - 2.0 %. Based on the conducted research, recommendations have been provided regarding the establishment of forecasts and limits for the extraction of aquatic resources from the Zaporizhzhia (Dnipro) reservoir for the year 2024. Conclusions: The Zaporizhzhia (Dnipro) reservoir has potential for the development of fishing, fish farming, and aquaculture in the Prydniprovsky region. The research results suggest that limits can be set on the catch of certain fish species: bream- up to 210 tons, pike-perch - up to 42 tons, roach - up to 350 tons, and perch - up to 138 tons. However, the catch of silver carp, bleak, sprat, herbivorous fish, and sun-perch is recommended to be unrestricted. The forecasted catch of crayfish is within 1 ton. The catch of other aquatic resources should also be conducted within forecasted levels